Emergency Department Visits, Care, and Outcome After Stroke and Myocardial Infarction During the COVID-19 Pandemic Phases - Amy Y.X. Yu, MD, MSc (Elsevier, 2021)
Background: It is not known if initial reductions in hospitalization for stroke and myocardial infarction early during the coronavirus disease–2019 pandemic were followed by subsequent increases. We describe the rates of emergency department visits for stroke and myocardial infarction through the pandemic phases. Methods: We used linked administrative data to compare the weekly age- and sex-standardized rates of visits for stroke and myocardial infarction in Ontario, Canada in the first 9 months of 2020 to the mean baseline rates (2015-2019) using rate ratios (RRs) and 95% confidence intervals (CIs). We compared care and outcomes by pandemic phases (pre-pandemic was January-March, lockdown was March-May, early reopening was May-July, and late reopening was July-September). Results: We identified 15,682 visits in 2020 for ischemic stroke (59.2%; n = 9279), intracerebral hemorrhage (12.2%; n = 1912), or myocardial infarction (28.6%; n = 4491). The weekly rates for stroke visits in 2020 were lower during the lockdown and early reopening than at baseline (RR 0.76, 95% CI [0.66, 0.87] for the largest weekly decrease). The weekly rates for myocardial infarction visits were lower during the lockdown only (RR 0.61, 95% CI [0.46, 0.77] for the largest weekly decrease), and there was a compensatory increase in visits following reopening. Ischemic stroke 30-day mortality was increased during the lockdown phase (11.5% pre-coronavirus disease; 12.2% during lockdown; 9.2% during early reopening; and 10.6% during late reopening, P = 0.015). Conclusion: After an initial reduction in visits for stroke and myocardial infarction, there was a compensatory increase in visits for myocardial infarction. The death rate after ischemic stroke was higher during the lockdown than in other phases. Résumé: Contexte: Nous ignorons si les réductions des taux d'hospitalisations pour un AVC et un infarctus du myocarde observées au début de la pandémie de coronavirus de 2019 ont été suivies d'une hausse de ces taux. Nous décrivons ici les taux de visites aux services des urgences pour un AVC et un infarctus du myocarde pendant toutes les phases de la pandémie. Méthodes: À partir de données administratives couplées, nous comparons les taux hebdomadaires de visites pour un AVC et un infarctus du myocarde, normalisés en fonction de l’âge et du sexe, en Ontario, au Canada, effectuées pendant les neuf premiers mois de 2020, avec les taux moyens de base (2015-2019), en utilisant des ratios des taux (RR) et des intervalles de confiance (IC) à 95 %. Nous avons comparé les soins et les issues selon les phases de la pandémie (avant la pandémie : de janvier à mars; confinement : de mars à mai; début de la réouverture : de mai à juillet; phase tardive de la réouverture : de juillet à septembre). Résultats: Nous avons répertorié 15 682 visites effectuées en 2020 pour un AVC ischémique (59,2 %; n = 9 279), une hémorragie intracérébrale (12,2 %; n = 1 912) ou un infarctus du myocarde (28,6 %; n = 4 491). Les taux hebdomadaires de visites pour un AVC effectuées en 2020 étaient inférieurs pendant la période de confinement et le début de la réouverture comparativement à la période de base (RR : 0,76; IC à 95 % : 0,66-0,87 pour la plus grande baisse hebdomadaire). Les taux hebdomadaires de visites pour un infarctus du myocarde étaient inférieurs pendant la période de confinement seulement (RR : 0,61; IC à 95 % : 0,46-0,77 pour la baisse hebdomadaire la plus importante); une hausse compensatrice du nombre de visites a été notée après la réouverture. Le taux de mortalité à 30 jours des suites d'un AVC ischémique était plus élevé pendant la période de confinement (11,5 % avant la pandémie de coronavirus; 12,2 % pendant le confinement; 9,2 % au début de la période de réouverture; 10,6 % pendant la phase tardive de la réouverture, p = 0,015). Conclusion: Après une réduction initiale du nombre de visites motivées par un AVC et un infarctus du myocarde, on a noté une hausse compensatrice du nombre de visites motivées par un infarctus du myocarde. Le taux de mortalité des suites d'un AVC ischémique était plus élevé pendant la période de confinement que pendant les autres périodes.